2009
DOI: 10.1007/s11999-008-0523-x
|View full text |Cite
|
Sign up to set email alerts
|

Acetabular Orientation: Anterolateral Approach in the Supine Position

Abstract: The anterolateral approach in the supine position provides excellent visualization of the acetabulum. The main advantage of the approach, a low dislocation rate, has been demonstrated in the literature, while the purported disadvantage of abductor dysfunction has not been clearly delineated in the literature. The technique requires meticulous attention to preservation of the gluteus medius and minimus tendons. Impingement and dislocation are avoided by careful attention to the preparation of acetabulum, critic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…They found that acetabular cup orientation showed no significant differences between the three surgical approaches. Rothman [ 19 ] thought that the operative approach affects the planned orientation of the acetabulum, primarily anteversion. Further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…They found that acetabular cup orientation showed no significant differences between the three surgical approaches. Rothman [ 19 ] thought that the operative approach affects the planned orientation of the acetabulum, primarily anteversion. Further research is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques for alignment of the acetabular cup remain controversial [44]. The ideal inclination and anteversion in THA are different for every patient [19]. Although Lewinnek's 'safe zone' is the most well known, others have suggested alternative and tighter limits [7,32,45].…”
Section: Discussionmentioning
confidence: 99%
“…Although post-operative dislocation rates have been reported to be as high as 2%-11% [7,[15][16][17] the most recent Australian data suggest a rate of less than 1% [18]. Correct positioning of the acetabular cup has also been reported to be an important factor in preventing component wear after THA [5,12,14,15,[19][20][21][22][23][24][25][26][27][28][29][30].…”
mentioning
confidence: 99%
“…The patient is placed in supine position. The minimally invasive Watson-Jones approach is utilized for reduced soft-tissue damage [16]. The capsule is split but not resected.…”
Section: Surgical Technique and Follow-up Treatmentmentioning
confidence: 99%